Niveles de colesterolemia y su relación con el sobrepeso en pacientes hipertensos que acuden al hospital Kokichi Otani de Vilcabama - Espinoza Peñaloza, Karen Yarima (2014)
Nowadays, overweight and obesity, associated with hypercholesterolemia, are a serious public health problem, caused by inappropriate lifestyles, which have been adopted in recent decades, such as the consumption of fast food, intake of high fat foods, added to the lack of continuous physical exercise. According to the World Health Organization (WHO), globally hypercholesterolemia causes 2.6 million deaths1. For this reason, the study was done on hypertensive patients attending the Vilcabamba Hospital, and whose goal was to quantify levels of total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL) and triglycerides, in order to relate total cholesterol to overweight. The study was implemented on 60 patients who satisfied the inclusion criteria. The resulting values were obtained from the spectrophotometers outcome (enzymatic- colorimetric method), and the degree of overweight was acquired by body mass index (BMI). The main findings of the study were as follows: 80% of hypertensive patients showed high total cholesterol levels; with regard to overweight, 68%, corresponding to 41 patients, were in this condition. From the hypercholesterolemia-overweight relation, was found that in 38 out of 41 patients diagnosed with hypertension and overweight, that is to say in 93%, hypercholesterolemia was associated with being overweight. Keywords: total cholesterol, overweight, hypertension.